The Sea Has (No) Borders: Ocean Zoning in Coastal Tonga - Brown Pulu, Teena; Amoamo, Rewi; Meredith, Nikolase; Tonga, Sylvester (Taylor and Francis Group, 2026)
In response to the socio-economic pressures of climate change, seen locally in declining inshore fisheries and deteriorating coral reefs, forty-nine coastal villages across the small island nation of Tonga have established community-managed marine protected areas to regulate fishing and sustain marine life. This visual essay offers behind-the-scenes reflections on creating short documentaries with and for the coastal villages of Tefisi and Makave in the Vava’u Islands of northern Tonga. Told from the perspectives of New Zealand–Tongan production crew members Rewi Amoamo and Nikolase Meredith, with contributions from their interviewer, Sylvester Tonga, the essay shares their storytelling alongside photographs that show how they made sense of sea borders through their interactions and collaborations with these coastal communities. The pictorial work centres on marine zoning practices that divide village coastlines into restricted fishing areas and no-take zones, boundaries that, on the water, are invisible and marked only by the occasional buoy. Twelve photographs capture the embodied experience of filming with fishers and fisheries officers within their shifting seascapes, where the borders of the ocean are both real and imagined.
Keywords: 451312 Pacific Peoples media, film, animation and photography; 451599 Pacific Peoples environmental knowledges not elsewhere classified; 451807 Pacific Peoples community-based research; 451317 Pacific Peoples research methods; 451307 Pacific Peoples ethics